Optimization of mix proportion of super-early-strength cement grouting material and experimental study on its working performance - Xiaokai Niu; He Wang; Zhitian Xie; Wei Song; Mingxing Li; Chentao Xu (Ain Shams Engineering Journal)
This paper investigates the effect of a novel super-early-strength cement grout composite on water leakage in the shield section of metro tunnels in operation. The physical and mechanical properties of the slurry were analyzed under varying water-cement ratios, amorphous calcium aluminate content, and admixture content by orthogonal test method. The corresponding relationships and internal correlation between parameter variables and the resulting properties were also explored. The results indicated that as the water-cement ratio and water-reducing agent content increased, the fluidity and water-elution rate of the slurry also increased, whereas cellulose ether showed an inverse effect. Furthermore, an increase in the amorphous calcium aluminate content significantly reduced the slurry’s setting time and enhanced its compressive strength in both early and late stages, demonstrating a clear coagulation-promoting and strengthening effect. Field applications confirmed that the amorphous calcium aluminate grouting material effectively mitigates water leakage in subway tunnels, proving its practical utility.